PENGARUH TIKTOK DAN FACEBOOK TERHADAP PARTISIPASI POLITIK PEMUDA DALAM PEMILIHAN UMUM 2024 DI DESA SUKANDEBI KEC. NAMAN TERAN KAB. KARO - Br Pelawi, Karina Mega Liasta; Siagian, Nalom; Degodona, L. Primawati (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
This study aims to analyze the influence of social media use, especially TikTok and Facebook, on youth political participation in the 2024 General Election in Sukandebi Village, Naman Teran District, Karo Regency. Social media has become the main platform for youth to obtain political information, discuss, and express their political preferences. The research method used is a quantitative approach with a causal associative research type. Data were collected by distributing questionnaires to 60 respondents consisting of youth in Sukandebi Village. Data analysis was carried out using statistical methods with multiple linear regression tests to determine the effect of TikTok and Facebook on youth political participation. The results showed that the use of TikTok and Facebook had a significant influence on youth political participation. TikTok plays a greater role in increasing youth involvement through interactive and easily accessible political content, while Facebook provides a more in-depth discussion space related to political issues. The coefficient of determination (R²) of 65.4% indicates that the TikTok and Facebook variables are able to explain most of the variability in youth political participation, while the rest is influenced by other factors.